Association between dietary vitamin B1 intake and stroke risk in older patients: a retrospective cross-sectional study - Shitu Zhuo; Zhenjie Chen; Lichao Ye; Jixing Chen; Zheng Yu; Meili Yang (BMC Neurology)
Abstract Background Stroke is associated with vitamin B12, folate, and vitamin B1 (VitB1); however, large-scale data supporting the association between VitB1 and stroke risk are lacking. In this study, we aimed to investigate the correlation between VitB1 intake and stroke risk in U.S. adults. Methods This retrospective study examined American adults using data from the National Health and Nutrition Examination Survey (NHANES). We analyzed data collected from eight NHANES conducted between 2003 and 2018, focusing on 15,381 participants aged ≥ 60 years. After excluding participants with missing information, the study comprised 11,724 individuals. All data were analyzed using univariate and multivariate logistic regression methods, restricted cubic spline, and sensitivity analyses. Results A total of 11,724 people were investigated in this survey. Dietary VitB1 levels were higher in the non-stroke group than in the stroke group (p < 0.001). Multivariate analysis revealed that VitB1 intake (as a continuous variable) and stroke risk exhibited an inverse association, with odds ratios (ORs) of 0.71 (95% confidence interval [CI]: 0.61, 0.82) and 0.72 (95% CI: 0.61, 0.84) in the crude model and Model 1, respectively. According to the fully adjusted model, each unit increase in VitB1 intake was linked to a 37% reduction in stroke risk (OR = 0.63, 95% CI: 0.48, 0.83); that is, the greater the VitB1 intake, the lower the stroke risk. Conclusions These findings indicate that lower dietary VitB1 intake was associated with an increased risk of stroke in older individuals, highlighting the potential importance of adequate dietary thiamine intake in stroke prevention strategies for the aging population.